Increased Light Harvesting by Structured Cell Interconnection Ribbons: An Optical Ray Tracing Study Using a Realistic Daylight Model. (August 2016) - Holst, Hendrik; Schulte-Huxel, Henning; Winter, Matthias; Blankemeyer, Susanne; Witteck, Robert; Vogt, Malte R.; Booz, Thomas; Distelrath, Fabian; Köntges, Marc; Bothe, Karsten; Brendel, Rolf
Abstract: A key for increasing the module efficiency is improved light harvesting. The structuring of solar cell interconnection ribbons (CIR) is a promising option for improved light harvesting as it can easily be integrated into current module production. We perform ray tracing simulations of complete PV modules in 3D exhibiting geometric features such as profiled CIR and surface textured cells. We evaluate the increase in module performance by a light harvesting string (LHS) under realistic irradiation conditions with respect to angular and spectral distribution. Using the realistic irradiation for a location in Germany, a location at the polar circle and a location at the equator we simulate the enhancement of short-circuit current density J sc resulting from the use of LHS. Our results show J sc gains between 1.00% and 1.86% depending on the location and module orientation. We demonstrate the applicability of our model by comparing measurements and simulations for a one-cell module that we measure and simulate under various angles of the light incidence.